2017
DOI: 10.1021/acs.iecr.7b02124
|View full text |Cite
|
Sign up to set email alerts
|

Continuous, High-Throughput Flash-Synthesis of Submicron Food Emulsions Using a Confined Impinging Jet Mixer: Effect of in Situ Turbulence, Sonication, and Small Surfactants

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Within this range of hydrodynamic conditions, the smallest droplet sizes (∼2 μm) were obtained at the highest jet flow rate (610 g/min) regardless of the type of emulsifier employed. Dilute emulsions of average droplet diameters below 700 nm were reported elsewhere, 20 but these could only be produced by coupling CIJM operation with sonication.…”
Section: Introductionmentioning
confidence: 99%
“…Within this range of hydrodynamic conditions, the smallest droplet sizes (∼2 μm) were obtained at the highest jet flow rate (610 g/min) regardless of the type of emulsifier employed. Dilute emulsions of average droplet diameters below 700 nm were reported elsewhere, 20 but these could only be produced by coupling CIJM operation with sonication.…”
Section: Introductionmentioning
confidence: 99%
“…The local shear stress and micromixing performance can be modulated by using hybrid reactor systems combined with different intensification method. Impinging streams has been recognized for a long time which can achieve very effective micromixing within an extremely short residence time when keeping the feeding rate steady [10,11]. Localized turbulent eddies and strong shear stress can be enhanced by violent collision between impinging streams [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the smallest droplet size (~2 µm) was achieved approaching the highest jet flow rates, independently from the type of surfactant used. More recently, it has also been shown that CIJs processing allowed the production of dilute emulsions having an average droplet dimension within the nano-size range (~700 nm) but only if coupled with an ultrasound treatment (Siddiqui et al, 2017). An additional study investigated the use of CIJs for the production of emulsions with dispersed phase content up to 80%, in the surfactant (Tween20)-poor and -rich regime, hydrodynamic conditions as well as residence times (Tripodi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%